The Feminine Principle in Ivo Andrić’s The Ivory Woman - Ahmetagić, Jasmina M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
In The Ivory Woman, Andrić uses dreams to thematize his protagonist’s key problem, that is, one important aspect of relationships between men and women, along with signals of generalization (the protagonist’s namelessness, the absence of specification of his social standing and duties) that are present in the story. The transformation that the ivory figurine experiences, by becoming a woman of flesh and blood in the protagonist’s dream, is given in the framework of all the elements that are, according to C. G. Jung, essential for understanding the dreamer’s unconscious experience: his life situation, current state of mind, and his interpretation of his own experience, so we also interpreted this transformation in this context. This is a meaningful, nightmarish dream, in which the protagonist meets an archetypal figure, the anima, his inner woman, who has in fact enshrouded his entire inner space. The protagonist’s possessedness by the anima is mirrored in his quickly-changing moods, in the ill will that dominates his life, in the manner that he tells his story, as well as in the fact that his objectivity had been lost in the sea of irrationality. The fantastic narrative, which we interpreted as the protagonist’s escape from facing himself, is based on the motif of the demonic woman, which is one of the typical negative forms of the anima. The dream confronts the protagonist with what he doesn’t know about himself: he is the one sabotaging his emotional relationships.